In situ survey of life cycle phases of the coccolithophore Emiliania huxleyi ( Haptophyta ) - Miguel J. Frada; Kay D. Bidle; Ian Probert; Colomban de Vargas (Environmental Microbiology, 2012)
Summary The cosmopolitan coccolithophore Emiliania huxleyi is characterized by a strongly differentiated haplodiplontic life cycle consisting of a diploid phase, generally bearing coccoliths (calcified) but that can be also non‐calcified, and a non‐calcified biflagellated haploid phase. Given most studies have focused on the bloom‐producing calcified phase, there is little‐to‐no information about non‐calcified cells in nature. Using field mesocoms as experimental platforms, we quantitatively surveyed calcified and non‐calcified cells using the combined calcareous detection fluorescent in situ hybridization (COD‐FISH) method and qualitatively screened for haploid specific transcripts using reverse transcription‐PCR during E. huxleyi bloom successions. Diploid, calcified cells formed dense blooms that were followed by the massive proliferation of E. huxleyi viruses ( Eh Vs), which caused bloom demise. Non‐calcified cells were also detected throughout the experiment, accounting for a minor fraction of the population but becoming progressively more abundant during mid‐late bloom periods concomitant with Eh V burst. Non‐calcified cell growth also paralleled a distinct window of haploid‐specific transcripts and the appearance of autotrophic flagellates morphologically similar to haploid cells, both of which are suggestive of meiosis and sexual life cycling during natural blooms of this prominent marine phytoplankton species.